The Relationship between Fear of COVID-19 and Self-Medication and the Rate of Antibiotic Use in Patients Referred to COVID-19 - Faraji, Fatemeh; Jalali, Rostam; Salari, Nader (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Introduction. The coronavirus pandemic can cause anxiety and stress among people, which can make them practice self-medication. This study aimed to investigate the relationship between fear of corona and self-medication and antibiotics use. Methods. In a convenience sampling method, 250 people referring to COVID-19 centers including 16-hour comprehensive health services in Kermanshah, Iran, who tested positive and were not hospitalized were extracted from the SIB system. Data collection tools include three questionnaires including corona fear questionnaire, self-medication questionnaire, and self-medication by antibiotic questionnaire and an information form including demographic characteristics. Data were analyzed by SPSS version 25. Results. The prevalence of self-medication was 59.6%. There was a significant correlation between self-medication and gender (P value <0.05) and education level (P value <0.05); the most common reason for self-medication was easy access to medicines through pharmacy drug stores. The mean score of fear of corona was higher in women and those who were not in a good financial position due to a lack of suitable economic status to see a doctor. Conclusion. There was a direct and significant relationship between self-medication and self-medication by antibiotics. 59.6% of the participants used medicines themselves, buying over-the-counter in pharmacies. Also, there was a statistically significant difference between the mean score of corona fear in terms of not having a suitable economic status to see a doctor. This indicates that the lack of proper economic status among people with the coronavirus positive test to see a doctor increases the fear of the disease.